2018
DOI: 10.1038/s41427-018-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Multistage redox reactions of conductive-polymer nanostructures with lithium ions: potential for high-performance organic anodes

Abstract: Conducive polymers have a wide range of applications originating from their π-conjugated systems. The redox reactions of conductive polymers with doping and dedoping of anions have been applied to cathodes for charge storage. In contrast, the redox reactions with cations have not been fully studied in anodes for charge storage. Here, we found that the nanostructures of conductive polymers, such as polypyrrole (PPy) . The introduction of a carboxy group to the pyrrole and thiophene rings enhanced the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Morphologies in sub‐micrometer scales contribute to ensure the diffusion of electrolyte solution. As for organic anode, the nanoparticles of polypyrrole and polythiophene with carboxy groups showed the enhanced specific capacity . This previous work implied the importance of not only the morphology but also the energy level of lowest unoccupied molecular orbital (LUMO) for the capacity.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Morphologies in sub‐micrometer scales contribute to ensure the diffusion of electrolyte solution. As for organic anode, the nanoparticles of polypyrrole and polythiophene with carboxy groups showed the enhanced specific capacity . This previous work implied the importance of not only the morphology but also the energy level of lowest unoccupied molecular orbital (LUMO) for the capacity.…”
Section: Introductionmentioning
confidence: 86%
“…Control of reaction potential and enhancement of specific capacity are achieved by molecular design of organic cathodes. Exploration of organic anode as an alternate of graphite has been rapidly developed during the past decade (Tables S1, S2 and Figure S1, Supporting Information) . Carboxy group on π‐conjugated molecules shows reversible reaction with lithium ion (Li + ) around 1.5 V versus Li/Li + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic compounds also have the advantages of structural diversity, [22] biocompatibility, and environmental-friendliness. [8,23] Organic anodes have shown superior lithium storage capacity and excellent rate capabilities, e.g., maleic acid [24] can deliver a capacity of 900 mAh g À1 over 500 cycles, and polythiophenebased polymers [25] deliver capacities of 960 mAh g À1 at 20 mA g À1 . The stability of polypyrrole electrodes over 1000 cycles has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[114] Thus, state-of-the-art investigations have been mainly focused on conjugated polymers (conductive polymers can be also regarded as a type of conjugated polymers) as well as polymers with multiple redox-active carbonyl groups. [115][116][117][118][119][120][121][122][123][124][125] Therefore, this thesis will mainly focus on these two types of polymers. Surprisingly, recent progress showed that the electrochemical performances including energy density, power density and cycling stability of redox-active polymers are comparable to or even superior than the conventional inorganic materials.…”
Section: Hypothesismentioning
confidence: 99%